Tip of the iceberg : immunohistochemical markers reveal malignant transformation underneath a vocal polyp surface = Vrh ledene sante : maligna transformacija ispod površine glasnica otkrivena imunohistokemijskim markerima - Braut, Tamara (Array, 2021)
Novel molecular techniques including markers of laryngeal carcinogenesis could improve the difficult diagnosis of a wide array of laryngeal polypoid changes. The case reported herein shows that not every clinically diagnosed vocal fold polyp is a benign lesion as mostly considered in the literature. Further assessment including carcinogenesis markers detected a nest of micro-invasive squamous cell carcinoma. Therefore, we recommend biopsy backed up with immunohistochemical analysis whenever there is a suspicious polypoid formation in order to exclude or confirm a malignant transformation because of the possibility of multi-focal growth in the active laryngeal epithelium.